The Lordiphosa denticeps species group (Diptera: Drosophilidae) in China, with redescriptions of four known species and descriptions of nine new species - Katoh, Takehiro K.; Zhang, Guang; Toda, Masanori J.; Zhang, Wen-Xia; Gao, Jian-Jun (Zootaxa, 2018)
Based on specimens collected from Yunnan, Xizang, and Taiwan in China, nine new species of the Lordiphosa denticeps species group, L. mikioides sp. nov., L. kimurai sp. nov., L. anthophilia sp. nov., L. yangi sp. nov., L. tibetica sp. nov., L. medogensis sp. nov., L. hamatispina sp. nov., L. secula sp. nov., and L. spatulata sp. nov., were described and four known species, L. denticeps (Okada & Sasakawa), L. neokurokawai (Singh & Gupta), L. ramula Zhang, and L. tripartita (Okada), were redescribed. In addition, we provided a key to all species of this species group. Males of three new species, L. mikioides, L. kimurai, and L. anthophilia, have distinct sex-combs consisting of black, stout teeth on the 1st and 2nd tarsomeres of foreleg; the large, longitudinal sex-comb on the 1st tarsomere is similar to those seen in the L. miki species group and the subgenus Sophophora Sturtevant of the genus Drosophila Fallén. Two of these and another new species were collected at flowering Impatiens L. (Balsaminaceae) stands: all specimens of L. anthophilia and L. medogensis directly from flowers, and some specimens of L. kimurai by net sweeping. The presence of large, longitudinal sex-combs and the flower-visiting habit were reported for the first time in the L. denticeps group.